2009
DOI: 10.1007/s11144-009-0089-y
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted heterogeneous catalysis: effects of varying oxygen concentrations on the oxidative coupling of methane

Abstract: The oxidative coupling of methane was investigated over alumina supported La 2 O 3 /CeO 2 catalysts under microwave dielectric heating conditions at different oxygen concentrations. It was observed that, at a given temperature using microwave heating, selectivities for both ethane and ethylene were notably higher when oxygen was absent than that in oxygen/methane mixtures. The differences were attributed to the localised heating of microwave radiation resulting in temperature inhomogeneity in the catalyst bed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Furthermore, the differences found in the selectivity and yield towards C 2 were more noticeable in the absence of oxygen. 37 The aforementioned results clearly highlight that the use of microwave radiation as the heating source for the OCM process can enhance the yield towards C 2 hydrocarbons. To explain the positive impacts derived from microwave heating, the presence of hotspots in the catalytic bed has been suggested.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the differences found in the selectivity and yield towards C 2 were more noticeable in the absence of oxygen. 37 The aforementioned results clearly highlight that the use of microwave radiation as the heating source for the OCM process can enhance the yield towards C 2 hydrocarbons. To explain the positive impacts derived from microwave heating, the presence of hotspots in the catalytic bed has been suggested.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 82%
“…Furthermore, the differences found in the selectivity and yield towards C 2 were more noticeable in the absence of oxygen. 37…”
Section: Introductionmentioning
confidence: 99%
“…These results led to the conclusion that continuation of the oxidation of ethane to CO x is inhibited. Oxidative coupling of methane was investigated by Ni et al over alumina supported La 2 O 3 /CeO 2 catalysts under microwave dielectric heating conditions at different oxygen concentrations [91]. It was observed that, at a given temperature using microwave heating, selectivity for both ethane and ethylene was notably higher when oxygen was absent than that in oxygen-methane mixtures.…”
Section: Oxidative Coupling Of Methanementioning
confidence: 99%
“…In addition, it is capable of being upscaled to the commercial level. Therefore, several works have reported the use of microwave radiation as a surface treatment process for producing ordered porous materials 27‐33 . Bond et al 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several works have reported the use of microwave radiation as a surface treatment process for producing ordered porous materials. [27][28][29][30][31][32][33] Bond et al 34 investigated the effect of microwave heating on the properties and activity of alumina-supported Ni catalysts in OCM reaction and compared these catalysts with those obtained by conventional heating. The results showed that the distribution of Ni on the support was much more uniform in the microwaved catalysts.…”
Section: Introductionmentioning
confidence: 99%